Preparation of wheat straw for fermentation under the influence of the electromagnetic field of a tesla transformer - Klendiy, P. B. (Energy and Automation, 2025)
The most common waste of agricultural production is straw of various crops and in particular wheat straw. During energy shortages, straw can be used as an energy resource in two ways: the first is direct combustion and obtaining thermal energy, and the second is its fermentation. In addition to obtaining biogas, highly mineralized organic fertilizer will also be obtained, which, when applied to the soil, will improve its fertility. As can be seen, the second method of using straw is more rational, but requires more complex equipment and a scientific approach to the methanogenesis process, since straw contains lignin, which gives it a rigid structure and makes it resistant to biological decomposition. Therefore, before fermentation, it is necessary to pre-treat the straw to destroy lignin and give microorganisms access to cellulose and hemicellulose polysaccharides. There are different methods for the degradation of straw, namely: mechanical, chemical, biological, physical, thermal or combined. The use of one or another method requires a technical and economic justification. That is, it is necessary to take into account the specific energy consumption, the cost of equipment, chemicals and the environmental friendliness of the process. To change the structure of straw, you can use high-frequency electromagnetic fields generated by a Tesla transformer. Before processing, straw is crushed and soaked in tap water and then exposed to a high-frequency electromagnetic field.Under the influence of a high-frequency electromagnetic field, the destruction of cell organelles of straw occurs, which will improve and accelerate the fermentation process, since complex compounds such as polymers are broken down and dissolved into monomer units through an enzymatically catalyzed reaction with water. Also, under the influence of a high-frequency electromagnetic field, changes occur not only in the tissues that are directly affected, but also systemically in remote tissues of the stem. Key words: high-frequency electromagnetic field, wheat straw, Tesla transformer, energy efficiency